Simulation of Structure and Energies of NinAlm Nanoclusters (n + m = 13) by Molecular Dynamics - Rojas T., Justo (2005)
By simulation with the Molecular Dynamics method and the thermal temper technique, the more stablegeometric structures and their respective energy were determined in the Nin Alm (n + m = 13)nanoclusters. The atomic interaction in the cluster was modelized with the Embeded Atom Method (EAM)(the Voter & Chen version). The most stable geometric structures of the cluster and their minimal energywere obtained from 200 generating spatial coordinates along the high energy path. The initial internalenergy is higher than the melting temperature of the cluster. The thermal temper technique was neededto remove slowly the internal kinetic energy from the clusters. The more stable clusters have a regularicosahedral geometrical structure.